Isolation and Identification of Candida albicans, Macrorhabdus ornithogaster, and Giardia spp. in Captive Pet Birds Referr ed to Aban Veterinary Clinic - Sobhani, S; Behrouzi Nasab, O; YarahmadiKhorasani , M; Fadayi, FS (Journal of the Hellenic Veterinary Medical Society, 2026)
Fungal and parasitic infections pose significant health risks to avian populations, particularly under conditions of immunosuppression or poor husbandry. This study investigated the prevalence of Candida albicans, Macrorhabdus ornithogaster, and Giardia spp. in 756 birds referred to a veterinary clinic over a two-year period (2023–2025). Fecal samples were analyzed via wet-mount microscopy, Gram staining, and clinical assessment to classify infections as mild, moderate, or severe. Results indicated C. albicans as the most prevalent pathogen (20.3% positivity), with severe cases concentrated in cockatiels and mynahs. M. ornithogaster infections were rarer (5% positivity), though an unusual predominance of intermediate cases in canaries suggested potential host-specific susceptibility. Giardiasis was detected in 40.6% of samples, primarily as mild infections (23.1%), with severe manifestations being rare (1.1%). Species-specific disparities were evident, with African grey parrots, pigeons, and finches showing no infections, while cockatiels and mynahs exhibited heightened vulnerability. These findings underscore the role of species-specific factors, immune status, and husbandry practices in disease manifestation. The study highlights the need for targeted surveillance in high-risk species and further investigation into atypical presentations, such as M. ornithogaster in canaries. Improved diagnostic protocols and management strategies are essential to mitigate these infections in avian populations.